Corrosion Inhibiting Mechanism of Nitrite Ion on the Passivation of Carbon Steel and Ductile Cast Iron for Nuclear Power Plants - K. T. Kim; H. W. Kim; H. Y. Chang; B. T. Lim; H. B. Park; Y. S. Kim (Advances in Materials Science and Engineering)
While NaNO2 addition can greatly inhibit the corrosion of carbon steel and ductile cast iron, in order to improve the similar corrosion resistance, ca. 100 times more NaNO2 addition is needed for ductile cast iron compared to carbon steel. A corrosion and inhibition mechanism is proposed whereby NO2- ion is added to oxidize. The NO2- ion can be reduced to nitrogen compounds and these compounds may be absorbed on the surface of graphite. Therefore, since nitrite ion needs to oxidize the surface of matrix and needs to passivate the galvanic corroded area and since it is absorbed on the surface of graphite, a greater amount of corrosion inhibitor needs to be added to ductile cast iron compared to carbon steel. The passive film of carbon steel and ductile cast iron, formed by NaNO2 addition showed N-type semiconductive properties and its resistance, is increased; the passive current density is thus decreased and the corrosion rate is then lowered. In addition, the film is mainly composed of iron oxide due to the oxidation by NO2- ion; however, regardless of the alloys, nitrogen compounds (not nitrite) were detected at the outermost surface but were not incorporated in the inner oxide.